2021
DOI: 10.3390/insects12050453
|View full text |Cite
|
Sign up to set email alerts
|

Mitogenome Analysis of Four Lamiinae Species (Coleoptera: Cerambycidae) and Gene Expression Responses by Monochamus alternatus When Infected with the Parasitic Nematode, Bursaphelenchus mucronatus

Abstract: We determined the mitochondrial gene sequence of Monochamus alternatus and three other mitogenomes of Lamiinae (Insect: Coleoptera: Cerambycidae) belonging to three genera (Aulaconotus, Apriona and Paraglenea) to enrich the mitochondrial genome database of Lamiinae and further explore the phylogenetic relationships within the subfamily. Phylogenetic trees of the Lamiinae were built using the Bayesian inference (BI) and maximum likelihood (ML) methods and the monophyly of Monochamus, Anoplophora, and Batocera g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 76 publications
1
11
0
Order By: Relevance
“…In this study, the monophyly of Lamiinae was highly supported, which had been confirmed in previous studies [ 8 , 9 , 10 , 11 , 12 , 13 , 51 , 61 ]. We also studied the phylogenetic relationships between some tribes among Lamiinae, and the monophyly of Lamiini was supported (BS = 100; PP = 1).…”
Section: Resultssupporting
confidence: 90%
See 1 more Smart Citation
“…In this study, the monophyly of Lamiinae was highly supported, which had been confirmed in previous studies [ 8 , 9 , 10 , 11 , 12 , 13 , 51 , 61 ]. We also studied the phylogenetic relationships between some tribes among Lamiinae, and the monophyly of Lamiini was supported (BS = 100; PP = 1).…”
Section: Resultssupporting
confidence: 90%
“…Souza et al (2020), who performed the first, relatively dense phylogenetic systematic assessment of Lamiinae, supported Phytoeciini as a synonym of Saperdini [ 13 ]. Further, the phylogenetic tree ( Figure 3 in Zhang et al (2021)) of 30 species of Lamiinae based on the nucleotide dataset of the 13PCGs of mitogenomes showed the same result [ 61 ].…”
Section: Resultsmentioning
confidence: 94%
“…Mega 7.0 was also used to calculate the genetic distance. We calculated the AT content and relative synonymous codon usage rate (RSCU) of the three genomes [ 16 ] using PhyloSuite v.1.2.2 [ 51 ]. With reference to invertebrate genetic codes, the nucleic acid sequences of the 13 PCGs were translated into amino acid sequences [ 16 , 52 ].…”
Section: Methodsmentioning
confidence: 99%
“…We calculated the AT content and relative synonymous codon usage rate (RSCU) of the three genomes [ 16 ] using PhyloSuite v.1.2.2 [ 51 ]. With reference to invertebrate genetic codes, the nucleic acid sequences of the 13 PCGs were translated into amino acid sequences [ 16 , 52 ]. The three mt genomes were deposited in GenBank with accession numbers OK265109–OK265111.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation